Developing wheat lines for rust resistance through Imperata cylindrica mediated chromosome elimination Doubled Haploidy technique: A Review: Doubled haploidy in wheat - Patial, Madhu; Verma, Ritika (Journal of Cereal Research, 2023)
Emergent food security issues for the rising population are an alarming concern. Thus, enhancing the productivity of the major food crops like wheat against different biotic and abiotic stress are targets on priority throughout the world. For wheat, rust diseases (leaf rust, stem rust and stripe rust) have been a devastating threat. To manage the disease, cultivation of rust resistant wheat cultivars is economically and environmentally sustainable approach. Different conventional breeding approaches have been used for the development of rust resistant wheat varieties. However, these conventional breeding tools are lengthy so to develop rust resistant lines in short time with lesser number of breeding cycles double haploidy (DH) technique has turned up as a boon for the breeders. Among different DH techniques, so far wheat x maize wide hybridization is reported to be the most effective method. However, the unsynchronized flowering of maize with that of wheat makes it a second choice in front of Imperata cylindrica which is a perennial wild grass easily found around the wheat fields. Also, it has higher frequency of haploid embryo development and regeneration than that of maize. The wheat DH breeding research programme for development of rust resistant lines has speeded up with the development of genetic stocks like DH-1 at ICAR-IARI, regional Station, Shimla (H.P) and many other resistant lines added to the wheat breeding programme of the station. However, extensive research, industrial collaborations and efficient protocol integrating the conventional breeding programmes are required for the exploration of this wild grass for wheat rust resistance breeding via DH technique.